Which Preschool Skills Predict School Readiness? - Oliveira, Inês; Duarte, Nuno; Vian, Frederica; Lopes, Patrícia; Pereira, Susana; Afonso, Silvia (Gazeta Médica, 2024)
School readiness (SR), the ability or preparedness of children to start schooling, depends on multiple factors, such as personal traits, sociocultural and familiar aspects, school context, education regulation and inclusion policies. Children who start schooling more prepared are most likely to achieve a higher academic level. Our objectives was to identify which preschool skills predict SR and to summarize general recommendations to consider when assessing SR. Research in data base PubMed, using the key words: “preschool”, “school readiness”, “social functioning”, “motor skills”, “mathematics”, “language”, “comprehension of the world”, “attention”. Consultation of the following Education and Health guidance: “Orientações Curriculares para a Educação Pré-Escolar da DGE”, “Norma Técnica da DGS para o PNSIJ”. Children’s social and emotional skills in preschool impact positively their academic skills. Visual perception, visual motor integration and motor coordination are essential to SR, namely to Reading, Writing and Mathematics. Global and fine motor skills cause longitudinal effects to Speech, Reading and Mathematics. Phonological awareness predict success in learning how to read. Numeral system acuity, mapping accuracy and the ability to control and keep attention at preschool are predictable of school success. Comprehension of the world is the strongest predictor for Reading and Science skills. It is important to assess SR on several occasions throughout children’s development, in a multidisciplinary approach. Prognosis is better when difficulties are detected at an early stage, thus allowing a directed intervention. The decision of delaying schooling must always consider biological, psychological and social variables, as well as school resources.